An Empirical Analysis of Unit Trust Performance in Singapore - Chia, Joseph H. H. (Institutional Knowledge at Singapore Management University, 2000)
The Singapore government’s recent strategic plan to develop the financial sector has placed much emphasis on the fund management industry. In this paper we examine the unit trust performance in Singapore in the 90s. Our results show that fund managers in general performed poorly in security analysis and market timing. However, they performed fairly well in risk-adjusted returns and generally maintained well-diversified portfolios. We find that there is little consistency in the performance ranking of the evaluated portfolios, although there is evidence of repeat performance of some top funds. Our analysis also shows that fund managers could indeed make excess returns above the risk-free rate in the medium- to long-term. Thus, unit trusts can be an ideal investment for small investors seeking sufficient diversification.